GOVERNMENT’S ATTEMPT TO PREVENT UNFAIR BUSINESS COMPETITION PRACTICES IN INDONESIA: COMPARISON ON REGULATION OF THE COMMISSION FOR THE SUPERVISION OF BUSINESS COMPETITION - Rachella Azalia (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Joint venture in Indonesia has been regulated through Government Regulation No. 20 of 1994 concerning Ownership of Shares of Companies Established in the Framework of Investment and Presidential Decree no. 32, 33 and 34 of 1992 in which a cooperation between foreign capital and national parties intended by the government to provide protection and the role or participation of national private parties in the implementation of foreign investment in Indonesia. Foreign Investment in Indonesia must be in the form of a Limited Liability Company based on Indonesian law and domiciled within the territory of the Republic of Indonesia, unless otherwise stipulated in the Law. This is due to the function of the PT itself, namely the limitation of liability for shareholders. With the proliferation of Foreign Investment implementation in Indonesia, the Government has arranged to continue to provide equal opportunities for every citizen to actively participate in the investment sector. The method of research is normative legal research and type of data analysis used is a qualitative approach with literature studie. Result, one of the government's efforts to prevent monopolistic practices is to oblige business actors to make a notification or notification to the Business Competition Supervisory Commission (Komisi Pengawas Persaingan Usaha).